2001
DOI: 10.1302/0301-620x.83b1.0830033
|View full text |Cite
|
Sign up to set email alerts
|

Femoral condylar lift-off in vivo in total knee arthroplasty

Abstract: We carried out weight-bearing video radiological studies on 40 patients with a total knee arthroplasty (TKA), to determine the presence and magnitude of femoral condylar lift-off. Half (20) had posterior-cruciate-retaining (PCR) and half (20) posterior-cruciate-substituting (PS) prostheses. The selected patients had successful arthroplasties with no pain or instability. Each carried out successive weight-bearing knee bends to maximum flexion, and the radiological video tapes were analysed using an interactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 0 publications
4
58
1
Order By: Relevance
“…Previous studies observed liftoff from 50 % to 86 % of cruciate-retaining TKA [7,14,26]. The average amount of condylar liftoff in the gap-balancing group was 1.3 mm, which is comparable with other study groups [7,14], in which an average liftoff between one and two millimetres is described. An increased midflexion instability in the gap-balancing group, however, could not be detected clinically up to the latest follow-up.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies observed liftoff from 50 % to 86 % of cruciate-retaining TKA [7,14,26]. The average amount of condylar liftoff in the gap-balancing group was 1.3 mm, which is comparable with other study groups [7,14], in which an average liftoff between one and two millimetres is described. An increased midflexion instability in the gap-balancing group, however, could not be detected clinically up to the latest follow-up.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore a too tight or too loose PCL might have contributed to lift-off. Previous studies observed lift-off up to 50 %-86 % of cruciate-retaining total knee arthroplasties [27,31,32]. The average amount of condylar lift-off was 0.87 mm, which is low compared to other study groups [27,31] where an average lift-off between one and two millimetres is described.…”
Section: Discussionmentioning
confidence: 62%
“…A second limitation is the authors' inability to state, with 100% certainty, that all of the kinematic findings observed in this analysis are only limited to variations in surgical technique. Previous kinematic analyses performed in our laboratory have documented substantial kinematic variances are common following TKA [6][7][8]23]. Multiple factors influence kinematics including technique type and quality, implant design, and variances in the individuals tested (motion, stability, alignment, etc.).…”
Section: Discussionmentioning
confidence: 95%
“…This was determined by performing digital measurements of the distances from the medial and lateral femoral condyles to the tibial tray [8] (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%